2017
DOI: 10.3390/s17061389
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Measuring Muscle Mechanics in Vehicle Collision Conditions

Abstract: The aim of the study was to evaluate a novel approach to measuring neck muscle load and activity in vehicle collision conditions. A series of sled tests were performed on 10 healthy volunteers at three severity levels to simulate low-severity frontal impacts. Electrical activity—electromyography (EMG)—and muscle mechanical tension was measured bilaterally on the upper trapezius. A novel mechanical contraction (MC) sensor was used to measure the tension on the muscle surface. The neck extensor loads were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…The dynamic response of the volunteers was comparable to the previous studies of low-severity frontal impacts. The mean head excursion was significantly influenced by the awareness and was decreased for the aware trials to 140.8 ± 38 mm ( Table 1 ), compared to 168 ± 35 mm at the peak deceleration of the sled (2.6 g) in the previous study [ 36 ]. Beeman et al [ 11 , 12 , 13 ] observed a 124 ± 9 mm head excursion at 2.5 g for relaxed volunteers in the driver’s position with the arms acting against the steering wheel.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The dynamic response of the volunteers was comparable to the previous studies of low-severity frontal impacts. The mean head excursion was significantly influenced by the awareness and was decreased for the aware trials to 140.8 ± 38 mm ( Table 1 ), compared to 168 ± 35 mm at the peak deceleration of the sled (2.6 g) in the previous study [ 36 ]. Beeman et al [ 11 , 12 , 13 ] observed a 124 ± 9 mm head excursion at 2.5 g for relaxed volunteers in the driver’s position with the arms acting against the steering wheel.…”
Section: Discussionmentioning
confidence: 87%
“…This study is based on the experimental data from the sled tests performed and partially described by Krašna et al [ 36 ]. In addition, signal- and data-processing methods are revised for this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations